O papel dos estágios supervisionado na formação dos professores: análise dos anos iniciais do ensino fundamental, educação infantil e gestão da educação - Nascimento, Thaylane Cavalcante do (Brasil, 2024)
End Course Work (TCC) presents the importance of supervised internships in teacher training, focusing on the Early Years of Elementary School, Early Childhood Education and Education Management. Through a detailed analysis of the practical experiences obtained in each of these internships, the study aims to highlight how these experiences contribute to the comprehensive training of future educators, providing a comprehensive and practical view of the teaching profession. During the internship, interns have the opportunity to apply pedagogical theories in practice, adapt to the needs of students and create effective teaching strategies, in addition to observing practices in a reflective manner. This direct contact with the school environment is essential for building a solid foundation of knowledge and skills that will be used throughout their careers. Therefore, internships in the early years of elementary school, early childhood education and education management reveal the depth and scope of the benefits of this training. Through this experience, it is noted that this stage favors professionalization and prepares future educators to work in the area of education in an effective and competent manner. The practices experienced at each stage of the internship contributed significantly to academic training, and the results obtained from the observations carried out will enrich the educational profession. It is concluded that supervised internships are essential for the training of future educators, as they allow them to apply theories in practice and develop essential skills for teaching. Experiences in the classroom and in school management strengthen theoretical knowledge and prepare interns for the challenges of the profession, contributing significantly to a solid and effective academic training. Each observation carried out was a unique opportunity to seek to improve pedagogical practices, allowing professionals to apply these learnings to their real experiences in the classroom.